Production of Fungal Mycelia in a Temperate Coniferous Forest Shows Distinct Seasonal Patterns - Štursová, Martina; Kohout, Petr; Human, Zander Rainier; Baldrian, Petr (Journal of fungi (Basel, Switzerland), 2020)
In temperate forests, climate seasonality restricts the photosynthetic activity of primary producers to the warm season from spring to autumn, while the cold season with temperatures below the freezing point represents a period of strongly reduced plant activity. Although soil microorganisms are active all-year-round, their expressions show seasonal patterns. This is especially visible on the ectomycorrhizal fungi, the most abundant guild of fungi in coniferous forests. We quantified the production of fungal mycelia using ingrowth sandbags in the organic layer of soil in temperate coniferous forest and analysed the composition of fungal communities in four consecutive seasons. We show that fungal biomass production is as low as 0.029 µg g-1 of sand in December-March, while it reaches 0.122 µg g-1 in June-September. The majority of fungi show distinct patterns of seasonal mycelial production, with most ectomycorrhizal fungi colonising ingrowth bags in the spring or summer, while the autumn and winter colonisation was mostly due to moulds. Our results indicate that fungal taxa differ in their seasonal patterns of mycelial production. Although fungal biomass turnover appears all-year-round, its rates are much faster in the period of plant activity than in the cold season.
Keywords: fungal ecology; metabarcoding; mycelial growth; soil fungi; ectomycorrhiza; temperate forest; Picea abies